The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1980
DOI: 10.3171/jns.1980.53.6.0749
|View full text |Cite
|
Sign up to set email alerts
|

The value of decompression for acute experimental spinal cord compression injury

Abstract: A clip compression method was used to produce acute spinal cord compression injury in rats. The force and duration of the spinal cord compression were independently varied, and functional recovery of the cord was assessed using the inclined plane technique. Mathematical modeling produced a curve defining the relationship between force, duration, and functional recovery for each week after injury. The study clearly showed the beneficial effect of decompression and that increasing either the force or duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
1
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(101 citation statements)
references
References 8 publications
(1 reference statement)
6
93
1
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][14][15][16][17][18][19][20] Some of these events, together constituting the 'secondary injury', evolve very early after the trauma.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][14][15][16][17][18][19][20] Some of these events, together constituting the 'secondary injury', evolve very early after the trauma.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experimental data have demonstrated that neurological recovery is enhanced by early decompressive procedures. [14][15][16][17][18][19][20] On the other hand, early surgery can cause deterioration of respiratory, haemodynamic and neurological functions. In acute systemic trauma, there is a greater probability of failure of alignment and fusion, and surgical treatment may be precluded by the lack of specific equipment and experienced personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Based on existing preclinical studies, it is clear that ongoing compression of the spinal cord represents a form of secondary injury that can be attenuated by decompressive surgery [21][22][23][24][25][26][27][28][29][30][31]. It is also evident that the degree of neural injury is directly related to the duration of spinal cord compression and inversely related to the time elapsed from injury to surgical decompression.…”
Section: Preclinical Evidence For Surgical Decompressionmentioning
confidence: 99%
“…The role of decompression combined with stabilisation is still con troversial (Dolan et at., 1980;Karulas and Bedbrook, 1927;Ducker and Byrnes, 1979;Freeman, 1958;Meyer, 1977). In many cases Harrington instrumentation can produce an anatomical restoration of the vertebral column, (Flesch et at., 1977;Roy-Camille et at., 1976;Yosipovitch et at., 1977) but does it adequately decompress the spinal canal?…”
Section: Introductionmentioning
confidence: 99%
“…If so, should Harrington instrumenta tion be combined with decompression, whether from the anterior, the anterolateral, the posterolateral or the posterior approach? (Schmidek et at., 1977;Larson et at., 1976;Riska and Myllynen, 1981;Bohlman and Eismont, 1981;Dolan et at., 1980;Paul et at., 1977;Wang et at., 1979;Young et at., 1981). The purpose of this paper is to report the gradual evolution of a philosophy as it applies to spinal injuries at the thoracolumbar junction.…”
Section: Introductionmentioning
confidence: 99%